Comparative micromorphology of the seed surface of Solanum melongena L. (eggplant) and allied species - Zain Hassan, Sayed Mohamed; Lester, Richard N. (Universiti Pertanian Malaysia, 1990)
The seed surface microstructure of Solanum melongena L., S. incanum L. and some other species were examined using SEM. Seeds were given enzyme (Driselase) etching treatment prior to examination to sweep off the outer layer of cells which obscured observation. Most seeds were characterised by hair-like structures or fibrils which surrounded each cell and which are strands of thickening in the lateral walls of the outer epidermal cells of the testa. Seed coat structure of S. melongena and S. incanum was found to be highly uniform in the samples examined indicating a close relationship between them. The seed coat patterns of S. torvum Sw., S. tomentosum L., S. aethiopicum L., S. kwebense Br. and Wr. and S. cinereum R.Br. were considerably different not only from S. melongena and S. incanum but also between themselves which supports the distinctness of these taxa.